Performance of an agricultural engine using blends of diesel and ethanol - Estrada,Javier Solis (2016)
ABSTRACT: This research evaluated the performance of a diesel engine in an agricultural tractor, using Diesel S500 (B5) and mixture with 3% (ED3), 6% (ED6), 9% (ED9), 12% (ED12) and 15% (ED15) of hydrous ethanol. Variables evaluated were the power, torque, specific fuel consumption, torque reserve, speed reserve and elasticity index of engine. Results indicated that using B5 and ED3 the values of torque and engine power not differ, in addition, with the ED3 the fuel consumption was lower than 5.92%. Using ED12, power has reduced in 2.97%, compared with B5, while their fuel consumption had no difference. With ED15, the power was lower 6.30% and the fuel consumption increase 3.77%, both compared with B5. Torque reserve value was increased with increasing the ethanol content in B5, reducing the speed reserve and elasticity index of engine. Ethanol in Diesel S500 (B5) can be used as an alternative fuel in agricultural tractor engines without presenting high changes in the performance, since the ethanol content is at low percentages, up to 12%.